Toward an understanding of the anomaly in charge yield of Mo and Sn fragments in the fission reaction 238U(n,f) - Pasca H. Horia; Andreev A. V. Aleksandr Vasiljevich; Adamyan G. G. Gurgen Grigorjevich; Antonenko N. V. Nikolay Viktorovich; Lacroix D. (2018, 2018)
Title screen